INVESTIGATION OF QUALITY INDICATORS OF BREAD STICKS BASED ON FIRST GRADE WHEAT FLOUR, RYE FLOUR AND TABLE BEET POWDER - I. M. Rusina; I. M. Kalesnik (Современная наука и инновации)
The article presents the results indicating the prospects of using beet root powder as an enrichment component in the production of bread sticks based on first grade wheat flour and sifted rye flour. This conclusion is based on a significant degree of yeast activation by a suspension of table beet powder and an increase in gas formation during the fermentation period. Quality indicators of composite mixtures, dough and bread sticks based on first grade wheat flour sifted rye flour in ratios of 70 and 30 parts, 80 and 20 parts and table beet powder in the amount of 1-9% by weight of the flour mixture were studied. It was found that with an increase in the amount of enrichment additive in composite mixtures, titratable acidity slightly increased and humidity decreased. Baked products according to two variants of the ratios of wheat and rye flour had good organoleptic and physico-chemical parameters at powder dosages of 1-5% by weight of flour. A further increase in the content of the additive led to a deterioration in the appearance of bread sticks, difficulty in their breaking, and decreased wetness of products. There was no significant difference in the of the products of the two variants of composite mixtures at the same dosages of table beet powder. When comparing the quality characteristics of bread sticks according to two methods of dough making, traditional and with preliminary activation of yeast with a suspension of table beet powder, higher indicators were noted for the second method. The possibility of using beet root powder at a dosage of 5% by weight of wheat flour of the first grade and sifted rye flour in the ratio of 70 and 30 parts in the production of bread sticks is also substantiated by the results of a tasting analysis.